2006
DOI: 10.1186/1471-230x-6-41
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in socioeconomic differences in incidence rates of cancers of gastro-intestinal tract in Finland

Abstract: Background: The magnitude of socioeconomic differences in health varies between societies, and over time within a given society. We studied the association between social class and incidence of cancers of the gastro-intestinal tract over time in a large cohort in Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
60
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 90 publications
15
60
3
Order By: Relevance
“…A relationship between increased physical activity and reduced risk of colon cancer is supported by several studies [29]. In Sweden and Finland a positive association has been reported between education and colon cancer for men but not for women [12,25].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A relationship between increased physical activity and reduced risk of colon cancer is supported by several studies [29]. In Sweden and Finland a positive association has been reported between education and colon cancer for men but not for women [12,25].…”
Section: Discussionmentioning
confidence: 53%
“…Our findings show that Icelandic men and women with academic education have a 30% lower risk of stomach cancer than the individuals with a lower education level. In other countries, low socioeconomic status has been a strong risk indicator for stomach cancer [24,25]. Dietary factors like salt intake and consumption of fruits and red meat, as well as prevalence of Helicobacter pylori bacteria, may play a role but the social gradient of these exposures has not been fully explained [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides genetic predisposition, several risk factors are suggested to play a role in the development and progression of CRC, such as obesity, smoking, and diet (Dai et al, 2007;Guh et al, 2009;Harriss et al, 2009;Johnson et al, 2013). Males are more likely to be addicted to drinking, smoking, and suffer from more living pressure, which may account for the relative high incidence of all kinds of cancer, including colorectal cancer (Morris et al, 1991;Weiderpass et al, 2006;Ibfelt et al, 2013;Levi et al, 2013;Menvielle et al, 2013;Parise et al, 2013;Manser et al, 2014). At present, some scientists say that people's educational background and socioeconomic status also play a role in the unbalanced distribution of colorectal cancer (Morris et al, 1991;Weiderpass et al, 2006;Parise et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Males are more likely to be addicted to drinking, smoking, and suffer from more living pressure, which may account for the relative high incidence of all kinds of cancer, including colorectal cancer (Morris et al, 1991;Weiderpass et al, 2006;Ibfelt et al, 2013;Levi et al, 2013;Menvielle et al, 2013;Parise et al, 2013;Manser et al, 2014). At present, some scientists say that people's educational background and socioeconomic status also play a role in the unbalanced distribution of colorectal cancer (Morris et al, 1991;Weiderpass et al, 2006;Parise et al, 2013). Social inequalities result from a skewed distribution of material and nonmaterial goods among the members of the society, which is measured by the meritocratic triad of profession, income, and education (Menvielle et al, 2013;Manser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent three decades, adenocarcinoma has surpassed squamous cell carcinoma of esophagus in developed countries [18,24] . Our findings showed that SCC was the most frequent esophageal tumor (17 cases) followed by ADC (two cases).…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%